(untitled) (Journal of the College of Basic Education, 2023)
The study of comparative jurisprudential issues in the religious law of peoples and nations is one of the issuesThe mission is to know its antiquity, civilization, and originality, and that every people and nation adheres to its religion, tryingThe satisfaction of the Lord God through working with His legal teachings, especially the Jewish law represented byTorah and Islamic law represented by the Qur’an.In this research, we shed light on five comparative jurisprudential issues through a bookSheikh Al-Balaghi  (Guidance to the Religion of the Chosen One), and we clarified the similarities and differences in the light ofreligious law, and we wrote the Hebrew biblical texts and translated them into Arabic, as well asQuranic texts that the sheikh did not include in his book, and we will, God willing, study the bookSheikh Al-Balaghi  in its entirety compared to the future.